Manajemen Event Nyala Feminist Festival Solo dalam Meningkatkan Kesadaran Kesetaraan Gender - Syifana Cahya Pambudi; Riski Apriliani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Feminist festivals serve as a crucial arena for gender equality advocacy, yet research on their event management strategies as a form of communication remains limited. This study examines the Nyala Feminist Festival Solo (FNFS) as a case study in event management aimed at increasing awareness of gender equality. The research objective is to analyze how the FNFS event management strategy, from its planning to evaluation stages, functions as an effective feminist communication practice. This study employs a qualitative method with a case study approach, where data were collected through indepth interviews with the organizing committee and participants, documentary analysis, and the researcher's reflexivity. The findings indicate that FNFS implemented a strategy that transcends conventional event management; through the practice of cyberfeminism on social media and an event design centered on creating inclusive safe spaces, the festival successfully sparked a transformation of consciousness among its participants. On the other hand, significant challenges related to social sustainability were also identified, stemming from limited human resources. This research concludes that the success of a feminist event is measured not only by its external impact on the audience but also by its capacity to build a healthy and sustainable internal management system.